2005
DOI: 10.1002/j.2168-9830.2005.tb00857.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Group Processes, Performance, and Satisfaction in Face‐to‐Face Versus Computer‐Mediated Engineering Student Design Teams

Abstract: Industry often requires engineers to work in teams. Therefore, many university engineering courses require students to work in groups to complete a design project. Due to the increasingly global nature of engineering, opportunities for students to navigate the issues of distance, time, culture, language, and multiple perspectives associated with virtual teams are becoming particularly desirable. To understand students' experience with virtual teams in a graduate course on principles of lean manufacturing, a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Despite its potential benefits, studies of CSCL have reported unpredictable group behaviors, including: misunderstandings due to lack of nonverbal cues, increased negative behavior such as flaming, reduced group consensus, less satisfaction with process and outcomes, and low efficiency [4]. Some research studies [5] support the idea that students prefer faceto-face over computer-mediated meetings.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its potential benefits, studies of CSCL have reported unpredictable group behaviors, including: misunderstandings due to lack of nonverbal cues, increased negative behavior such as flaming, reduced group consensus, less satisfaction with process and outcomes, and low efficiency [4]. Some research studies [5] support the idea that students prefer faceto-face over computer-mediated meetings.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research suggests that learning can be best facilitated by scaffolded instruction that supports collaboration and interaction in authentic environments using state of the art tools and processes. 8 Scaffolds are defined as instructional and expert support in the guise of feedback, directions or guided instructional materials and tools embedded in instructional activities. Scaffolding has been identified as a powerful approach to support learning in complex collaborative environments.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…However, most existing engineering programs don't fully incorporate the learning opportunities for students to master technology-supported teamwork as a core element of the curriculum. 8,9 Also, we have found that in general, there is little understanding of the role of technology on supporting collaborative learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that most existing engineering programs don't fully incorporate the opportunity for students to master technology-supported teamwork as a core element of the curriculum. 4,5 In addition, courses that use team projects give little consideration to the cognitive and behavioral processes such as team building, clarifying goals and expectations, planning, communication, consensus building and conflict resolution; which hold the key to successful collaboration. 5,6 A recent review of research on engineering student teams suggests that our understanding of how best to cultivate collaboration amongst remote teams of students is largely underdeveloped 7 .…”
Section: A Qualitative Inquiry Into the Role Of Web-based Collaboratimentioning
confidence: 99%